DESIGN OF AN IOT-BASED AUTOMATIC MOSQUE DOOR SYSTEM USING PIR AND CAMERA SENSORS FOR SMART WORSHIP ACCESS - Annisa Rizqi; Dania Fitriyani; Ika Herni; Rozy Ilhami; M. Rahmadoni Khoiriansyah; Miftahul Jannah (Ninety Media Publisher, 2026)
Mosques and mushallas are worship facilities with high congregational activity, requiring a secure, comfortable, and efficient door access system. Manual door operation often causes several problems, such as doors not closing properly, noise caused by slamming doors, and high physical contact between users and the door. This study aims to design and develop an automatic door system based on Passive Infrared (PIR) sensors and surveillance cameras integrated with Internet of Things (IoT) technology to improve security and convenience in mosque and mushalla environments. The research method used is Research and Development (R&D), consisting of system requirement identification, hardware and software design, prototype implementation, testing, and evaluation. The system uses PIR sensors or cameras to detect the presence of worshippers, microcontrollers such as Arduino, ESP32, or Raspberry Pi as the control center, and servo motors or DC motors as automatic door actuators. The system is also equipped with a real-time notification feature through Telegram to send information and visual documentation to administrators. The results show that the system is capable of detecting movement, automatically opening and closing doors, and sending notifications along with visual documentation in real time. The system improves user convenience, reduces physical contact with doors, and facilitates remote security monitoring by administrators. In addition, the use of ESP32-CAM is considered effective and economical for implementing IoT-based automatic door systems.